2006
DOI: 10.1038/sj.bdj.4813149
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and sleeping partners' experience of treatment for sleep-related breathing disorders with a mandibular repositioning splint

Abstract: Aim To determine in detail the complications associated with the use of mandibular repositioning splints (MRS) to treat sleep-related breathing disorders. Method This prospective cross-sectional cohort study audits the management with mandibular repositioning splints of 121 patients suffering from sleep-related breathing disorders. Investigation of patients' and sleeping partners' perspectives on treatment was undertaken with the use of a questionnaire based study. Results Sixty-eight per cent of respondents r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Recently, appliances which allow the patient to control the advancement themselves have been used. 10,11 Previous research by Johnston 6 and Bates 8 has shown success rates of 76-84% and 70% respectively, using a monobloc design in non-apnoeic snorers. Recently, research in this area has taken into account the effects of the snoring on the patient's sleeping partner.…”
Section: N B R I E F Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, appliances which allow the patient to control the advancement themselves have been used. 10,11 Previous research by Johnston 6 and Bates 8 has shown success rates of 76-84% and 70% respectively, using a monobloc design in non-apnoeic snorers. Recently, research in this area has taken into account the effects of the snoring on the patient's sleeping partner.…”
Section: N B R I E F Researchmentioning
confidence: 99%
“…It has previously been shown that the use of these appliances provide a signifi cant improvement on the partner's sleep pattern. 6,8,12,13 Assessment of success utilising partners' views is a relatively new, but an important aspect in the provision of care. Bates and McDonald 8 have previously assessed sleeping partners with a specifi cally designed questionnaire.…”
Section: N B R I E F Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study of OA treatment among 121 patients with OSA found 64% of partners to report improvement in their sleep after 3 mo of treatment. 29 Among 62 partners who share a bedroom with patients with OSA treated with an OA, more than half reported improvements in their general well-being, mental energy, and sleep quality and less daytime sleepiness and disturbed sleep after 1 y of treatment. 30 In a comparative study of two OAs, 94% of partners (n = 16) reported improved sleep quality, quality of life, and personal relationship with the patient at 3-mo followup and these improvements were maintained at 2.5-to 4.5-y follow-up (n = 14).…”
Section: Oral Appliancesmentioning
confidence: 99%